3(5x+4)=7(-3x+12)

Simple and best practice solution for 3(5x+4)=7(-3x+12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(5x+4)=7(-3x+12) equation:



3(5x+4)=7(-3x+12)
We move all terms to the left:
3(5x+4)-(7(-3x+12))=0
We multiply parentheses
15x-(7(-3x+12))+12=0
We calculate terms in parentheses: -(7(-3x+12)), so:
7(-3x+12)
We multiply parentheses
-21x+84
Back to the equation:
-(-21x+84)
We get rid of parentheses
15x+21x-84+12=0
We add all the numbers together, and all the variables
36x-72=0
We move all terms containing x to the left, all other terms to the right
36x=72
x=72/36
x=2

See similar equations:

| x+56*2=5 | | 5(7x+4)=3(5x+6)+42 | | 4x-40=24x | | 5x-6=7(-7x+30) | | 11x-5=1/3 | | 1/3x-5=11 | | 2=(p-3)/(2) | | 4.9x-1.9=27. | | 5=6x-7=29 | | 17(x×52)=74 | | 2=2/p-3 | | 4^x=-82 | | 2/5(15b+15)=24 | | 7^x=(1/343) | | (6+x)^3=28 | | 46x+30=1000 | | 46x+30=513 | | 46x+30=76 | | -3(2x-6)+5(4x-5)=35 | | 3x-3=4-6 | | 3(3x+4)+2(2x+6)=63 | | 2x^2+3=8-3x | | x²+11x+24=0 | | -6(3x+6)=54 | | -3q-10/4=-7 | | 3x+6=6(6x+8)+123 | | 2(2x+5)+3(4x+6=76 | | 2.4(x+6)=-5.6+8 | | 3(3x-8)-4x+5=-4 | | -5p-9/6=-4 | | 15–3x=2-5x | | 4x+3=4(7x+4)+59 |

Equations solver categories